2019
DOI: 10.3892/etm.2019.8282
|View full text |Cite
|
Sign up to set email alerts
|

Role of lncRNA‑ATB in ovarian cancer and its mechanisms of action

Abstract: This study aimed to elucidate the role of long non-coding RNA activated by transforming growth factor-β (lncRNA-ATB) in ovarian cancer and its underlying mechanisms of action. Expression levels of lncRNA-ATB in ovarian cancer cell line SKOV3 and in a healthy human ovarian cell line were compared using reverse transcription-quantitative polymerase chain reaction (RT-qPCR). The results indicated that lncRNA-ATB was expressed at significantly higher levels in SKOV3 cells compared with the healthy cell line. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Long non-coding RNAs (lncRNAs) are endogenous and long non-coding RNA molecules (~200nt) that regulate gene expression by targeting miRNA or mRNA posttranscriptionally. [4][5][6][7] Increasing studies have revealed lncRNAs played crucial roles in tumorigenesis, metastasis and MDR. For example, lncRNA DANCR promotes tumor progression and cancer stemness features in osteosarcoma by upregulating AXL via miR-33a-5p inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are endogenous and long non-coding RNA molecules (~200nt) that regulate gene expression by targeting miRNA or mRNA posttranscriptionally. [4][5][6][7] Increasing studies have revealed lncRNAs played crucial roles in tumorigenesis, metastasis and MDR. For example, lncRNA DANCR promotes tumor progression and cancer stemness features in osteosarcoma by upregulating AXL via miR-33a-5p inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Long non‐coding RNAs (lncRNAs) could transcriptionally or post‐transcriptionally regulate expression and epigenetic levels of target genes, whose dysregulation are widely known to be involved in the development and progression of many cancers 9 . Large numbers of lncRNAs regulate tumor progression in ovarian cancer 10 . For example, lncRNA SNHG20 promotes tumor progression, 11 while AOC4P suppresses metastasis of ovarian cancer 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence indicates that early detection and prevention of ovarian cancer is an investigation priority as diagnosis at a local stage is accompanied with a 5-year relative survival rate of upper than 90% (Torre et al, 2018). There is considerable evidence showing that lncRNAs play critical roles in tumorigenesis process, invasion, and metastasis of ovarian cancer (Liu et al, 2020;Pa et al, 2020;Yuan et al, 2020). HOTAIRM1 has been proved to be aberrantly up/downregulated in some solid tumors (Zhang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%